Burnout in residents during the first wave of the COVID-19 pandemic: a systematic review and meta-analysis - Navinés, Ricard; Olive, Victoria; Hidalgo-Mazzei, Diego; Langohr, Klaus; Vieta, Eduard; Martin-Santos, Rocio (Frontiers in Psychiatry, 2024)
The high prevalence of burnout in resident physicians is expected to have increased as a result of the expansion of the pandemic. We conducted a systematic review with meta-analysis of studies done during the first wave of the COVID-19 pandemic on burnout in residents and potential associated risk factors.Methods: Searched was done in Web-of-Science, MEDLINE, Scopus, Lillac database (April 2020-October 2021), using a priori protocol based on PRISMA guidelines. The Newcastle Ottawa Scale was used to assess the risk of bias of the included studies. We estimated the pooled prevalence (95%CI) of burnout and prevalence ratio (95%CI) of each risk factor associated.We included 23 studies from 451 potential initial articles, written in English language, all were cross-sectional, anonymous online surveys; involving 4,998 responders (34%), 53.2% females, 51% R1-2, and 71% in direct contact with COVID-19 patients. Eighty-seven per cent presented low-to-moderate risk of bias. Publication bias was not shown. The estimated pooled prevalence of burnout was 40% (95%CI= 0.26 -0.57). Burnout was associated to psychiatry history (PR= 4.60, 95%CI= 1.06 -20.06). There were no differences by gender, civil status, children, year of residency, or time exposure to COVID-19.Discussion: Overall prevalence of burnout in residents during the first wave of the pandemic was in line with results described in this collective before the pandemic. The presence of psychiatry history was a potential burnout risk factor, suggesting a high vulnerability during the peak of stress period and the need of implement mental health surveillance for this subgroup.